1995
DOI: 10.1095/biolreprod53.2.321
|View full text |Cite
|
Sign up to set email alerts
|

Striking Changes in the Structure and Organization of Rat Fetal Membranes Precede Parturition1

Abstract: Premature rupture of fetal membranes can harm infant and mother. It is unclear whether structural changes predispose these membranes to breaking. We thus assessed rat visceral yolk sac placenta (VYSP) and amnion by light and by transmission electron microscopy on Days 18-21 of gestation. Light microscope sections were stained for connective tissue (extracellular matrix) components: collagen, glycoprotein, and glycosaminoglycans/proteoglycans. Some tissue was incubated with chondroitinase ABC. We observed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1996
1996
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Although animal data document homogeneous weakening of the FM over the entire surface with increasing gestation (Lei et al, , 1997Paavola et al, 1995;Parry et al, 1998), attempts to demonstrate similar gestational changes in human FM were unsuccessful (Manabe et al, 1991). Studies in which whole FM or randomly selected pieces were sampled showed high variability and no definite pattern of remodeling and apoptosis.…”
Section: Mapping Proceduresmentioning
confidence: 99%
“…Although animal data document homogeneous weakening of the FM over the entire surface with increasing gestation (Lei et al, , 1997Paavola et al, 1995;Parry et al, 1998), attempts to demonstrate similar gestational changes in human FM were unsuccessful (Manabe et al, 1991). Studies in which whole FM or randomly selected pieces were sampled showed high variability and no definite pattern of remodeling and apoptosis.…”
Section: Mapping Proceduresmentioning
confidence: 99%
“…Recent 1 data in the rat model suggest that the amnion, the component of the fetal membrane (FM) with the major tissue strength, undergoes collagen remodeling as gestation progresses [2,3]. Apoptosis has also been observed in rat amnion following end-gestational remodeling [3,4]. As a result of remodeling and apoptosis, the FM is postulated to weaken and be more susceptible to tearing near the end of gestation [3, 4,].…”
Section: Introductionmentioning
confidence: 99%
“…During labor, the membranes usually rupture, a process that has been attributed frequently to mechanical forces (1). Recently, we characterized the histological and ultrastructural features of the rat fetal membranes, the amnion and visceral yolk sac placenta, at the end of pregnancy and discovered striking changes in the cells comprising the membranes as well as the extracellular matrix before the onset of active labor (2). These structural changes were particularly marked in the amnion and included delamination of amnion epithelial cells from the amnion basement membrane, ultrastructural signs of apoptosis, and a dramatic loss of fibrillar collagen from the amnion matrix.…”
Section: Introductionmentioning
confidence: 99%
“…The goals of this study were to determine if cells of the amnion display characteristic biochemical features of apoptosis at term, including nuclear DNA fragmentation (3) and degradation of ribosomal RNA (4), and if these changes are associated with the activation of collagenolytic enzymes that degrade the primary amnion fibrillar collagen, type I collagen (2,5).…”
Section: Introductionmentioning
confidence: 99%